Active labor market policies - Crépon, Bruno; van den Berg, Gerard J. (Bonn, 2016)
"Active labor market policies are massively used with the objective being to improve labor market outcomes of individuals out of work. Many observational evaluation studies have been published. In this review, we critically assess policy effectiveness. We emphasize insights from recent randomized controlled trials. In addition, we examine policy effects that have not been the primary object of most of the past evaluations, such as anticipatory effects of advance knowledge of future treatments and equilibrium effects, and we discuss the actual implementation of policies. We discuss the importance of heterogeneity of programs and effects and examine the extent to which potential participants are interested in enrollment. We also discuss the assessment of costs and benefits of programs."